Virological Mechanisms in the Coinfection between HIV and HCV. (1st October 2015) - Liberto, Maria Carla; Zicca, Emilia; Pavia, Grazia; Quirino, Angela; Marascio, Nadia; Torti, Carlo; Focà, Alfredo
Abstract : Due to shared transmission routes, coinfection with Hepatitis C Virus (HCV) is common in patients infected by Human Immunodeficiency Virus (HIV). The immune-pathogenesis of liver disease in HIV/HCV coinfected patients is a multifactorial process. Several studies demonstrated that HIV worsens the course of HCV infection, increasing the risk of cirrhosis and hepatocellular carcinoma. Also, HCV might increase immunological defects due to HIV and risk of comorbidities. A specific cross-talk among HIV and HCV proteins in coinfected patients modulates the natural history, the immune responses, and the life cycle of both viruses. These effects are mediated by immune mechanisms and by a cross-talk between the two viruses which could interfere with host defense mechanisms. In this review, we focus on some virological/immunological mechanisms of the pathogenetic interactions between HIV and HCV in the human host.